Ne crimina remaneant impunita? Crime e justiça no território feudal de Genazzano (Estado Pontifício) entre a segunda metade do século XVI e a primeira do XVII - Santini, Francesco (2020)
The present study concerns crime and justice in the feudal territory of Genazzano, politically inscribed within the Papal States and their environs during the second half of the 16th century and the first half of the 17th. Through an analysis mainly based on criminal processes pertaining to the communities of Genazzano, Cave, and Paliano, produced by the court of the local auditor, we analyze the meaning of crime and justice for the individuals of that context. In this sense, approaching the question from a sociocultural perspective, we examine thoroughly some specific cases, though representative, verifying that, in the territory in question, controlled since the 12th century by the aristocratic family of the Colonna, crime, in general, occurred as consequence of the conflicts of relations between the various individuals: residents of varied statuses, seigniorial authorities, and the very lord Colonna. Justice was that dimension understood as the result of reparation or resolution of said conflicts, exercised within as well as outside the court. The court, as representative of the lord, performed the double role of repressive and judging power, adopting, however, a tendency that followed the leitmotiv of the Colonna of Genazzano-Paliano, that is, to keep the peace and the common good in the communities. Such posture is deduced from the answers that the lord gave the pleas of his subjects, to whom he practically always granted mercy, which seems to have counted only for those who belonged to the community. For foreigners, justice appeared differently: there was the need to prove a true interest in becoming a colonnese ‘citizen’, respecting and complying with certain sociocultural rules and practices. The present work confirms the maintenance, on the part of the Colonna, of strong feudal prerogatives, at least within the sphere of justice, for the lord, still in the middle of the 16th and 17th centuries, continued to exercise his right to judge those under his jurisdiction, taking from the papal power the prerogative of condemnation to capital punishment and granting mercies. Thus, for the lord, the importance of keeping this condition was substantial, because, through an authoritarian and paternalistic practice, he ensured and reproduced his power. At the same time, however, the subjects were aware of the possibilities that the seigniorial justice offered, using it largely as a resource. Thus, the social actors ‘danced’ the ‘dance of justice’, inside and outside the court: accusing and being accused; pleading, making peace and receiving mercy from the prince, without the certainty of the result, but knowing exactly the ‘movements’ that could yield them the final ‘applause’.